Identification of ligands and translation to clinical applications - Haberkorn, Uwe; Mier, Walter; Kopka, Klaus; Herold-Mende, Christel; Altmann, Annette (Journal of nuclear medicine, 2017)
Technologic advances in molecular biology and biotechnology are increasingly being used for the development of new tumor-targeting tracers. In oncology, major progress has recently been achieved with peptidic and proteinaceous compounds. The development of new biocompatible molecules relies on the identification and validation of new target structures in close conjunction with the application of novel techniques. The identification of lead compounds by these techniques is followed by the screening of various derivatives of these molecules. Hence, high-throughput methods that generate vast libraries of epitopes have been applied. These libraries are screened to identify the few variants that bind with a high affinity to the target structure. A key feature of this strategy is the large number of candidate molecules that can be identified. Further evaluation and optimization of these molecules requires characterization of structure-function relationships and subsequent improvement with respect to binding, internalization, and biodistribution through a rational design of corresponding analogs.